Laser-induced surface reconstruction to enhance interfacial bonding reliability of CFRP/titanium hybrid joints - Zhaoyi Liu; Hui Wang; Yizhe Chen; Lin Hua (Journal of Materials Research and Technology, 2024)
Adhesive bonding is widely used in aeronautical carbon fiber-reinforced polymer (CFRP)/titanium (Ti) alloy hybrid structures to satisfy the demands of high-strength and lightweight. The physicochemical properties of adherend surfaces significantly impact the bonding performance. In this study, laser-induced surface reconstruction (LISR) was designed for the reliable joining of Ti alloy and CFRP. A three-level-three-factor central composite design (CCD) approach-based response surface methodology (RSM) analysis was applied to statistically specify parameter optimization of the laser energy output. Surface morphology and wettability of CFRP ablated were studied. Chemical compositions were determined by X-ray photoelectron spectroscopy (XPS). Tensile-shear tests were performed, and fractured surfaces were analyzed. The tensile shear strength with LISR process has been improved by 19.1%, in comparison with that of mechanical grinding treatment. The cross-like texture based on designed geometric configuration was fabricated without damaging the underlying fibers, thus increasing the surface roughness and contact area at interface. The wettability transition mechanism was investigated, demonstrating that the hydrophilicity of reconstructed surfaces primarily attributes to the more polar groups (C–O, CO, etc.) on CF surfaces. This study provides a reliable surface treatment method for fabricating high-performance composite structures by adhesive bonding.